2021
DOI: 10.7861/fhj.2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

A new reality: Bedside geriatric teaching in an age of remote learning

Abstract: Population ageing poses many challenges in the landscape of general medicine. One of these is the requirement for more geriatricians to minimise future strain on healthcare systems. Previous studies have identified that, while demand for geriatricians is on the rise, interest among medical students for a career in geriatrics falls behind. We utilised a new augmented reality technology (the Microsoft HoloLens 2) to deliver students a remote bedside teaching experience. Features of this teaching included bi-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The articles discussed in this section ( Multimedia Appendix 3 [ 32 , 36 , 40 - 42 , 47 - 51 , 58 , 62 , 69 ]) are divided based on nonsurgical contexts, which include clinical skills, autopsy, and sonography, and surgical contexts, which include procedure observation, tool-specific training, simulations, and intraoperative learning. Of note, one-third (6/19, 32%) of the articles that involved education have been described in the previous section and will be briefly mentioned in this section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles discussed in this section ( Multimedia Appendix 3 [ 32 , 36 , 40 - 42 , 47 - 51 , 58 , 62 , 69 ]) are divided based on nonsurgical contexts, which include clinical skills, autopsy, and sonography, and surgical contexts, which include procedure observation, tool-specific training, simulations, and intraoperative learning. Of note, one-third (6/19, 32%) of the articles that involved education have been described in the previous section and will be briefly mentioned in this section.…”
Section: Resultsmentioning
confidence: 99%
“…The Microsoft HoloLens 2 allowed students to not only see through the clinician’s eyes using their personal devices but also simultaneously review overlaid 2D patient data and imaging. Rafi et al [ 47 ] featured a cardiovascular examination that was remotely spectated by final-year medical students. Using the Microsoft Teams application compatible with the HoloLens, the study measured student engagement in the form of written “chat” comments from students during the session [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surgical specialties have explored this potential extensively, with telesurgery tools such as Proximie and Virtual Interactive Presence and AR allowing remote experts to see the operating field of surgeons and interact using real-time annotation and labeling [36][37][38][39]. The nonsurgical specialties have also seen an emergence of AR to share views for remote shadowing in inpatient wards [40,41] and wound evaluations [42,43]. For emergency medicine, studies have shown that AR assists both remote emergency procedures and assessments through the use of a shared view, with trials focused on speed and performance [29,44,45].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Nine contributions [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] described the use of AR technology and the feasibility of using the HoloLens 2 headset to deliver remote bedside teaching or to enable 3D display for the facilitation of the learning process or in tele-mentoring and tele-consulting contexts.…”
Section: Ms Hololens 2 Applications In Medical and Healthcare Context...mentioning
confidence: 99%